Model supervisi klinis berfokus multikultural: supervisi hubungan interpersonal konselor dan staf kependidikan - Rezki Hariko; Indriyana Rachmawati (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
Performance collaboration between counselor and teacher or staff is urgentlyneeded in providing guidance and counseling services for students. This collaboration needs to be supervised, one of them by using multi-cultural focused clinical supervision. This supervisory activity emphasizes the aspect of recognizing the cultural differences that can arise between supervisors and supervisors who can influence the supervision activities. A supervisor needs to be aware of the perception bias that may affect the supervision activities. Supervisors should be reactive to cultural diversity in carrying out supervisory activities demonstrated through recognition of cultural differences between supervisors and supervisors, understanding the power of differences and initiating discussions on diversity. Supervisors must also be aware of obstacles in multicultural supervision, such as: perception bias and lack of supervision training.